HUBUNGAN KELINCAHAN DENGAN DRIBBLING BOLA PADA PERMAINAN SEPAK BOLA SISWA SMA NEGERI 1 LAWA - La Ode Muhamad Randi; Hasanuddin Jumareng; Badaruddin (Universitas Halu Oleo, 2021)
The purpose of this study was to determine the relationship between agility and ball dribbling in the soccer game of SMA Negeri 1 Lawa students. The problem formulation in this study is whether there is a relationship between agility and dribbling in the soccer game of SMA Negeri 1 Lawa students? The population in this study were 210 students of SMA Negeri 1 Lawa, consisting of 105 girls and 105 boys. The sample in this study amounted to 32 people who were taken by purposive sampling technique. That is, the sample is selected with the male gender in mind who has the criteria that the researcher wants. The instrument used to measure agility is the Right boomerang run test, which is carried out 2 times for each student while the instrument used to measure the dribbling ability of the ball is using a dodging obstacle. , which was done 2 times for each student. The research data were analyzed using the product moment statistical technique at the significant level of 0.05 where the results obtained from hypothesis testing showed that Rxy = 0.67> r table at the significant level 0.05 = 0.349. The coefficient of determination of agility with ball dribbling = 0.45 or 45% and the other 55% influenced by other physical condition factors. This research can conclude that there is a significant relationship between agility and ball dribbling in the soccer game of SMA Negeri 1 Lawa students.